Productivity Shocks and Delayed Exchange-Rate Overshooting - Christian Pierdzioch (Kiel Institute for World Economics (IfW), 2004)
This paper uses a 'new open economy macroeconomics' model to study the effect of a productivity shock on exchange rate dynamics. The special features of the model are that households' preferences exhibit a 'catching up with the Joneses' effect and that international financial markets are imperfectly integrated. Numerical simulations of the model are used to demonstrate that these features imply that, in an otherwise standard ?new open economy macroeconomics' model, a productivity shock can give rise to a delayed overshooting of the exchange rate.
Keywords: F31; F41; F32; 330; Productivity shock; Exchange rate overshooting; Overshooting; Neue Makroökonomik offener Volkswirtschaften; Produktivität; Schock; Konsuminterdependenz; Theorie; catching up with the Joneses